A method for measuring austenite content in steel
Through X-ray diffractometer and TOPAS software combined with Rietveld method, the steel specimens are accurately measured, which solves the problem of inaccurate measurement of austenite content in the prior art, and improves the measurement accuracy and result reliability.
Patent Information
- Application Number
- CN202210211311.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-05
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-03-05
AI Technical Summary
The prior art is difficult to accurately measure the austenite content in steel materials, which affects the mechanical properties and service life of the material.
X-ray diffractometer and TOPAS software combined with Rietveld method were used to perform phase-by-step grinding, polishing and phase-by-phase qualitative analysis of steel samples. Through the introduction of CIA data files and refining process, unit cell parameters are automatically or manually adjusted. to determine the volume fraction and mass fraction of austenite and martensite.
It improves the accuracy of measuring austenite content in steel, can accurately calculate the volume fraction and mass fraction of austenite, and enhances the reliability of the test results.
Smart Images

Figure CN114705704B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of X-ray diffraction test, and in particular relates to a method for measuring austenite content in steel. Background Art
[0002] After quenching, steel materials often have a certain amount of residual austenite, and the amount of austenite has an important influence on the mechanical properties and service life of the material. Therefore, in order to improve the mechanical properties and service life of steel materials, a reasonable heat treatment process must be adopted to control the austenite content in the material. How to accurately measure the austenite content in steel materials is an important topic for testers. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one object of the present invention is to provide a method for measuring austenite content in steel.
[0004] The technical solution of the present invention is as follows: A method for measuring austenite content in steel, characterized in that it comprises the following steps:
[0005] S1: Grind the steel sample to be tested step by step with metallographic sandpaper, and then polish it until the surface is smooth and clean;
[0006] S2: using an X-ray diffractometer to obtain an X-ray diffraction pattern and X-ray diffraction data of the steel sample polished in step S1;
[0007] S3: using X-ray analysis software to perform phase qualitative analysis on the X-ray diffraction pattern obtained in step S2 to determine whether martensite, austenite and a third phase other than martensite and austenite exist in the steel sample. If no third phase exists, proceed to the next step;
[0008] S41: according to the result of step S3, using Findit2008 software to export the corresponding cif data files of martensite and austenite in the output library, and using the cif data files as reference data for fitting;
[0009] S51: Open TOPAS software, click the "Load scan files" icon in the TOPAS software, import the original diffraction data file *.raw, and the X-ray diffraction spectrum and the spectrum to be fitted will appear at the bottom of the software;
[0010] S61: Import the required cif data files into TOPAS software;
[0011] S71: Select the original file and first select the light tube diffraction ray type "Emission Profile": *.lam;
[0012] S81: Select "Background" to perform background correction on the X-ray diffraction pattern, select the "Chebychev" polynomial as "refine", then select the "order" series, and then select "1 / X Bkg" as "refine";
[0013] S91: Select "Instrument", fill in "Primary radius" and "secondary radius"; select the detector type "point detector", and then select the slit specifications;
[0014] S101: Select "Corrections", select "Zero error" and "Sample displacement" in "Peak shift" respectively; set "LP factor" "Value" to "0" and "Code" to "Fix" in "Intensity Corrections"; set "Absorption" in "Sample Convolutions" to "refine";
[0015] S111: Select "Miscellaneous" and set "Conv.Steps" "Value" to "1";
[0016] S121: Click "Austenite structure" and "martenstite structure" in the TOPAS software to set the austenite and martensite unit cell parameters to "refine";
[0017] S131: Set the "Code" for atomic position in austenite and martensite structures to "Fix"
[0018] S141: Click the "Run" icon in the TOPAS software to refine the X-ray diffraction spectrum. The TOPAS software automatically refines the pattern. After the refinement is completed, the software interface will display the refinement error.
[0019] S151: Click "sample" in the software interface, and then click "Rpt / Text" to display the volume fraction and mass fraction of austenite in the sample respectively.
[0020] In step S3, the phase of the X-ray diffraction spectrum is qualitatively analyzed. If the third phase exists in the analysis result, the following steps are performed:
[0021] S42: according to the result of S3, using Findit2008 software to export the corresponding cif data files of martensite, austenite and the third phase in the output library, and using the cif data files as reference data for fitting;
[0022] S52: Open TOPAS software and import the required cif data files and X-ray diffraction data into TOPAS software;
[0023] S62: Manually adjust the unit cell parameters of martensite, austenite and the third phase;
[0024] S72: Select the original file and first select the light tube diffraction ray type "Emission Profile": *.lam;
[0025] S82: Select "Background" to perform background correction on the X-ray diffraction pattern, select the "Chebychev" polynomial as "refine", then select the "order" series, and then select "1 / X Bkg" as "refine";
[0026] S92: Select "Instrument", fill in "Primary radius" and "secondary radius"; select the detector type "point detector", and then select the slit specifications;
[0027] S102: Select "Corrections", select "Zero error" and "Sample displacement" in "Peak shift" respectively; set "LP factor" "Value" to "0" and "Code" to "Fix" in "Intensity Corrections"; set "Absorption" in "Sample Convolutions" to "refine";
[0028] S112: Select "Miscellaneous" and set the "Value" in "Conv.Steps" to "1";
[0029] S122: Click "Austenite structure", "martenstite structure" and "third phase" in the TOPAS software to set the unit cell parameters of austenite, martensite and third phase to "refine";
[0030] S132: Set the atomic position "Code" in austenite, martensite and third phase structures to "Fix";
[0031] S142: Click the "Run" icon in the TOPAS software to refine the X-ray diffraction pattern. The TOPAS software automatically refines the pattern. After the refinement is completed, the software interface will display the refinement error.
[0032] S152: Click "sample" in the software interface, and then click "Rpt / Text" to display the volume fraction and mass fraction of austenite, martensite and the third phase in the sample respectively.
[0033] Preferably, the specific content of step S2 is: placing the polished steel sample on a cleaned sample table, the X-ray tube of the X-ray diffractometer emits X-rays and irradiates the steel sample to produce a diffraction phenomenon, and the radiation detector of the X-ray diffractometer receives the X-ray photons of the diffraction line, and after amplification and processing by the measurement circuit, the corresponding X-ray diffraction spectrum and X-ray diffraction data are obtained.
[0034] Preferably, in step S2, the scanning method of the steel sample using the X-ray diffractometer adopts a step scanning mode, the X-ray tube target adopts a cobalt target, the working voltage is 35 kV, the working current is 40 mA, the 2θ scanning range is 50°-120°, the scanning mode is a stepping mode, the step length is 0.02°, and the scanning speed is 0.5° / min.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The present invention adopts the Rietveld method for a steel sample with preferred orientation, and uses TOPAS refinement software to perform structural refinement on an X-ray diffraction spectrum, in order to improve the accuracy of the test result when calculating the austenite content in the steel.
[0037] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work:
[0039] Figure 1 It is a schematic diagram of the present invention. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Please refer to the following drawings Figure 1 A method for measuring austenite content in steel according to an embodiment of the present invention is described, comprising the following steps:
[0042] S1: The steel sample to be tested is ground step by step with metallographic sandpaper, and then polished to a smooth and clean surface. The metallographic sandpaper used is a special sandpaper used for grinding in metallographic analysis in a physical laboratory. It is suitable for a metallographic grinder and is a water-resistant sandpaper.
[0043] S2: Use an X-ray diffractometer to obtain the X-ray diffraction pattern and X-ray diffraction data of the steel sample after polishing in step S1. X-ray diffractometer is a large-scale analytical instrument for qualitative and quantitative phase analysis and microstructural characterization of solid substances, especially crystalline substances, and is widely used in various disciplines. The wavelength of X-rays is similar to the spacing between atomic planes inside the crystal. The crystal can be used as a spatial diffraction grating for X-rays, that is, when a beam of X-rays is irradiated on an object, it is scattered by the atoms in the object, and each atom generates a scattered wave. These waves interfere with each other, resulting in diffraction. The superposition of diffraction waves results in the intensity of the rays being enhanced in some directions and weakened in other directions. By analyzing the diffraction results, the crystal structure can be obtained.
[0044] The specific measures of this step are to place the polished steel sample on a cleaned sample table, the X-ray tube of the X-ray diffractometer emits X-rays and irradiates the steel sample to produce diffraction phenomenon, and the radiation detector of the X-ray diffractometer receives the X-ray photons of the diffraction line. After amplification and processing by the measuring circuit, the corresponding X-ray diffraction spectrum and X-ray diffraction data are obtained, wherein the X-ray diffractometer is used to scan the steel sample in a step scanning mode, the X-ray tube target is a cobalt target, the working voltage is 35kV, the working current is 40mA, the 2θ scanning range is 50°-120°, the scanning mode is a step mode, the step length is 0.02°, and the scanning speed is 0.5° / min.
[0045] S3: Use X-ray analysis software to perform phase qualitative analysis on the X-ray diffraction pattern obtained in step S2 to determine whether martensite, austenite and a third phase other than martensite and austenite exist in the steel sample. If no third phase exists, proceed to the next step.
[0046] Specifically, steel is extracted from iron ore, also known as iron-carbon alloy, which is an alloy composed of iron (Fe) and carbon (C), silicon (Si), manganese (Mn), phosphorus (P), sulfur (S) and other small amounts of elements (Cr, V, etc.). By adjusting the content of various elements in steel and the heat treatment process (four fires: quenching, annealing, tempering, normalizing), a variety of metallographic structures can be obtained, so that steel has different physical properties. In the Fe-Fe3C system, a variety of iron-carbon alloys with different compositions can be prepared. Their equilibrium structures at different temperatures are different, but they are composed of several basic phases (ferrite F, austenite A and cementite Fe3C). These basic phases are combined in the form of mechanical mixtures to form a rich and colorful metallographic structure in steel.
[0047] Austenite is a lamellar microstructure of steel. Austenite is generally composed of equiaxed polygonal grains with twins inside the grains. The austenite grains are relatively small at the end of the heating transformation, and the grain boundaries are irregular arcs. After a period of heating or heat preservation, the grains will grow and the grain boundaries may tend to be straightened. Austenite is a high-temperature phase in the iron-carbon phase diagram, existing above the critical point A1 temperature, and is formed by the reverse eutectoid transformation of pearlite. When enough chemical elements that expand the austenite phase region are added to the steel, such as Ni, Mn, etc., austenite can be stabilized at room temperature, such as austenitic steel. Ferrite will transform into austenite at 912℃ to 1394℃, changing from a body-centered cubic structure to a face-centered cubic structure. Austenite has low strength, but its carbon solubility is large (it can dissolve 2.04% carbon at 1146℃). Austenitic stainless steel is often used in the food industry and surgical equipment.
[0048] Martensite is formed by rapid cooling (quenching) of austenite, in which case the carbon atoms dissolved in the austenite do not have time to diffuse out of the unit cell. When austenite reaches the martensitic transformation temperature (Ms), martensitic transformation begins and the parent austenite structure becomes unstable. When a certain temperature is kept constant below Ms, a small part of the austenite structure transforms rapidly, but it does not continue. Only when the temperature is further reduced, more austenite transforms into martensite. Finally, the temperature reaches the martensitic transformation end temperature Mf, and the martensitic transformation ends.
[0049] The difference between martensite and austenite is that martensite is a body-centered tetragonal structure, while austenite is a face-centered cubic structure. The transformation of austenite to martensite requires very little energy because the transformation is diffusionless and involves only a rapid and small atomic rearrangement.
[0050] S41: According to the result of step S3, the corresponding cif data files of martensite and austenite in the output library are exported using Findit2008 software, and the cif data files are used as reference data for fitting. The Findit used is an inorganic crystal structure database query software.
[0051] S51: Open TOPAS software, click the "Load scan files" icon in TOPAS software, import the original diffraction data file *.raw, and the X-ray diffraction spectrum and the spectrum to be fitted will appear at the bottom of the software. The TOPAS-Academic software used is a full spectrum analysis software specially designed for educational and scientific research units launched by Coelho Software of Australia based on the German Bruker-TOPAS software. It is used for advanced analysis of X-ray diffraction (XRD) spectra and sample crystal structures.
[0052] S61: Import the required cif data files into TOPAS software;
[0053] S71: Select the original file and first select the light tube diffraction ray type "Emission Profile": *.lam;
[0054] S81: Select "Background" to perform background correction on the X-ray diffraction pattern, select the "Chebychev" polynomial as "refine", then select the "order" series, and then select "1 / X Bkg" as "refine";
[0055] S91: Select "Instrument", fill in "Primary radius" and "secondary radius"; select the detector type "point detector", and then select the slit specifications;
[0056] S101: Select "Corrections", select "Zero error" and "Sample displacement" in "Peak shift" respectively; set "LP factor" "Value" to "0" and "Code" to "Fix" in "Intensity Corrections"; set "Absorption" in "Sample Convolutions" to "refine";
[0057] S111: Select "Miscellaneous" and set "Conv.Steps" "Value" to "1";
[0058] S121: Click "Austenite structure" and "martenstite structure" in the TOPAS software to set the austenite and martensite unit cell parameters to "refine";
[0059] S131: Set the "Code" for atomic position in austenite and martensite structures to "Fix"
[0060] S141: Click the "Run" icon in the TOPAS software to refine the X-ray diffraction pattern. The TOPAS software will automatically refine the pattern. After the refinement is completed, the software interface will display the refinement error.
[0061] S151: Click "sample" in the software interface, and then click "Rpt / Text" to display the volume fraction and mass fraction of austenite in the sample respectively.
[0062] In the above step S3, the phase of the X-ray diffraction spectrum is qualitatively analyzed. If the third phase exists in the analysis result, the following steps are performed:
[0063] S42: According to the results of S3, the corresponding cif data files of martensite, austenite and the third phase in the output library are exported using Findit2008 software, and the cif data files are used as reference data for fitting;
[0064] S52: Open TOPAS software and import the required cif data files and X-ray diffraction data into TOPAS software;
[0065] S62: Manually adjust the unit cell parameters of martensite, austenite and the third phase;
[0066] S72: Select the original file and first select the light tube diffraction ray type "Emission Profile": *.lam;
[0067] S82: Select "Background" to perform background correction on the X-ray diffraction pattern, select the "Chebychev" polynomial as "refine", then select the "order" series, and then select "1 / X Bkg" as "refine";
[0068] S92: Select "Instrument", fill in "Primary radius" and "secondary radius"; select the detector type "point detector", and then select the slit specifications;
[0069] S102: Select "Corrections", select "Zero error" and "Sample displacement" in "Peak shift" respectively; set "LP factor" "Value" to "0" and "Code" to "Fix" in "Intensity Corrections"; set "Absorption" in "Sample Convolutions" to "refine";
[0070] S112: Select "Miscellaneous" and set the "Value" in "Conv.Steps" to "1";
[0071] S122: Click "Austenite structure", "martenstite structure" and "third phase" in the TOPAS software to set the unit cell parameters of austenite, martensite and third phase to "refine";
[0072] S132: Set the atomic position "Code" in austenite, martensite and third phase structures to "Fix";
[0073] S142: Click the "Run" icon in the TOPAS software to refine the X-ray diffraction pattern. The TOPAS software automatically refines the pattern. After the refinement is completed, the software interface will display the refinement error.
[0074] S152: Click "sample" in the software interface, and then click "Rpt / Text" to display the volume fraction and mass fraction of austenite, martensite and the third phase in the sample respectively.
[0075] The invention discloses a method for measuring austenite content in steel. The Rietveld method is adopted for a steel sample with preferred orientation, and TOPAS refinement software is used to perform structural refinement on an X-ray diffraction spectrum, so as to improve the accuracy of the test result when calculating the austenite content in the steel.
[0076] In 1967, Rietveld proposed a method of structural refinement using full spectrum fitting, which started a new era of fundamental changes in diffraction data processing. The Rietveld method is a full spectrum fitting method, which uses the data spectrum of each step on the diffraction spectrum. The least squares method is used to adjust the structural atomic parameters and peak shape parameters so that the calculated peak shape fits the observed peak shape, that is, the weighted residual variance factor Rwp of the graph is minimized.
[0077] A 2θ diffraction pattern i The measured intensity y at point iis formed by the Bragg reflection, and the intensity y is calculated. ik It is the structural factor F that is calculated by accumulating the contributions of each Bragg reflection in its vicinity in the structural model. k 2 value and other factors, which can be expressed as
[0078]
[0079] Where S is the scale factor;
[0080] K represents the Miller index h, k, l of Bragg reflection;
[0081] P K is the preferential orientation function;
[0082] F k is the structure factor of the Kth Bragg reflection;
[0083] L k Contains Lorentz polarization and multiplicity factors;
[0084] Ф is the reflection peak shape function;
[0085] A is the absorption factor, and the effective absorption factor A varies with the geometric design of the diffractometer;
[0086] S r is the surface roughness factor;
[0087] E is the extinction factor;
[0088] yb i is the background strength at point i.
[0089] In the process of least squares full spectrum fitting, the residual value in the following formula should be minimized.
[0090] S=Σ i w i [y i -y ik ] 2 (2)
[0091] W i is the weight factor
[0092] The Rietveld refinement method has the following advantages: no need for standard sample calibration, high accuracy, high speed, no difficulties caused by spectral peak overlap due to the increase in physical phases, and the ability to correct systematic errors caused by factors such as preferred orientation and line broadening.
[0093] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for measuring austenite content in steel, characterized in that: The following steps are involved: S1: Grind the steel sample to be tested step by step with metallographic sandpaper, and then polish it until the surface is smooth and clean; S2: using an X-ray diffractometer to obtain an X-ray diffraction pattern and X-ray diffraction data of the steel sample polished in step S1; S3: using X-ray analysis software to perform phase qualitative analysis on the X-ray diffraction pattern obtained in step S2 to determine whether martensite, austenite and a third phase other than martensite and austenite exist in the steel sample. If no third phase exists, proceed to the next step; S41: according to the result of step S3, using Findit2008 software to export the corresponding cif data files of martensite and austenite in the output library, and using the cif data files as reference data for fitting; S51: Open TOPAS software, click the "Load scan files" icon in the TOPAS software, import the original diffraction data file *.raw, and the X-ray diffraction spectrum and the spectrum to be fitted will appear at the bottom of the software; S61: Import the required cif data files into TOPAS software; S71: Select the original file, first select the light tube diffraction ray type "Emission Profile": *.lam; S81: Select "Background" to perform background correction on the X-ray diffraction pattern, select the "Chebychev" polynomial as "refine", then select the "order" series, and then select "1 / X Bkg" as "refine"; S91: Select "Instrument", fill in "Primary radius" and "secondary radius"; select the detector type "point detector", and then select the slit specifications; S101: Select "Corrections", select "Zero error" and "Sampledisplacement" in "Peak shift" respectively; set "LP factor" "Value" to "0" and "Code" to "Fix" in "Intensity Corrections"; set "Absorption" to "refine" in "Sample Convolutions"; S111: Select "Miscellaneous" and set "Conv.Steps" "Value" to "1"; S121: Click "Austenite structure" "martenstite structure" in TOPAS software to set the austenite and martensite unit cell parameters to "refine"; S131: Set "Code" to "Fix" for atomic position in austenite and martensite structures S141: Click the "Run" icon in the TOPAS software to refine the X-ray diffraction pattern. The TOPAS software automatically refines the pattern. After the refinement is completed, the software interface will display the refinement error. S151: Click "sample" in the software interface, then click "Rpt / Text" to display the volume fraction and mass fraction of austenite in the sample respectively.
2. The method for measuring austenite content in steel according to claim 1, characterized in that: In step S3, the phase of the X-ray diffraction spectrum is qualitatively analyzed. If the third phase exists in the analysis result, the following steps are performed: S42: according to the result of S3, using Findit2008 software to export the corresponding cif data files of martensite, austenite and the third phase in the output library, and using the cif data files as reference data for fitting; S52: Open TOPAS software and import the required cif data files and X-ray diffraction data into TOPAS software; S62: Manually adjust the unit cell parameters of martensite, austenite and the third phase; S72: Select the original file, and first select the light tube diffraction ray type "Emission Profile": *.lam; S82: Select "Background" to perform background correction on the X-ray diffraction pattern, select the "Chebychev" polynomial as "refine", then select the "order" series, and then select "1 / X Bkg" as "refine"; S92: Select "Instrument", fill in "Primary radius" and "secondary radius"; select the detector type "point detector", and then select the slit specifications; S102: Select "Corrections", select "Zero error" and "Sampledisplacement" in "Peak shift" respectively; set "LP factor" "Value" to "0" and "Code" to "Fix" in "Intensity Corrections"; set "Absorption" to "refine" in "Sample Convolutions"; S112: Select "Miscellaneous" and set the "Value" in "Conv.Steps" to "1"; S122: Click "Austenite structure" "martenstite structure" "third phase" in TOPAS software to set the unit cell parameters of austenite, martensite and third phase to "refine"; S132: Set the "Code" of atomic position in austenite, martensite and third phase structure to "Fix"; S142: Click the "Run" icon in the TOPAS software to refine the X-ray diffraction pattern. The TOPAS software automatically refines the pattern. After the refinement is completed, the software interface will display the refinement error. S152: Click "sample" in the software interface, then click "Rpt / Text" to display the volume fraction and mass fraction of austenite, martensite and the third phase in the sample respectively.
3. The method for measuring austenite content in steel according to claim 1, characterized in that: The specific content of step S2 is: placing the polished steel sample on a cleaned sample table, the X-ray tube of the X-ray diffractometer emits X-rays and irradiates the steel sample to produce a diffraction phenomenon, and the radiation detector of the X-ray diffractometer receives the X-ray photons of the diffraction line, and after amplification and processing by the measurement circuit, the corresponding X-ray diffraction spectrum and X-ray diffraction data are obtained.
4. The method for measuring austenite content in steel according to claim 3, characterized in that: In step S2, the steel sample is scanned by an X-ray diffractometer in a step scanning mode, a cobalt target is used as the X-ray tube target, the working voltage is 35 kV, the working current is 40 mA, the 2θ scanning range is 50°-120°, the scanning mode is a stepping mode, the step length is 0.02°, and the scanning speed is 0.5° / min.
